A twisted nematic liquid crystal box, a display device and a preparation method thereof
By doping composite γ-Fe2O3 nanoparticles wrapped in oleic acid at a specific concentration in the liquid crystal, the problem of low transmittance of liquid crystal displays is solved, and the effect of significantly improving the electro-optical characteristics is achieved, and it is suitable for the mid- and low-end display fields.
Patent Information
- Application Number
- CN202210786949.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-07-04
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2042-07-04
AI Technical Summary
The low transmittance problem of existing liquid crystal displays leads to high energy consumption and uneco-friendly, and the existing technical solutions are costly, which is not suitable for production and market demand in the mid- and low-end display fields.
The electro-optical characteristics of the twisted nematic liquid crystal cell are improved by doping composite γ-Fe2O3 nanoparticles with a specific concentration of oleic acid in the liquid crystal.
The transmittance of the liquid crystal display is improved, especially when the doping concentration is 0.0304 wt%, the transmittance can reach about 43%, which significantly improves the electro-optical characteristics.
Smart Images

Figure CN115167047B_ABST
Abstract
Description
Technical Field
[0001] This document relates to the field of optoelectronic technology, and in particular to a twisted nematic liquid crystal box, a display device, and a preparation method. Background Art
[0002] The electro-optical characteristics of liquid crystal display products are an important technical indicator, which directly affects the transmittance, contrast, drive and other issues of the display. When light is emitted through the components inside the screen (components designed to meet the requirements of optical indicators such as viewing angle), the light intensity will be greatly weakened. Liquid crystal displays usually use high-power backlight sources to make up for the defect of low transmittance, which also causes high energy consumption and environmental problems. In order to improve the contrast of liquid crystal displays, the most effective way is to reduce the transmittance in the dark state and use optical compensation films, but the transmittance in the bright state will also decrease, and the utilization rate of light will be reduced.
[0003] At present, the technologies to solve the low transmittance problem of LCDs include: high transmittance intelligent LCD dimming film production technology, coplanar conversion display mode, development of high transmittance color film materials, development of high transmittance liquid crystal materials, etc. However, these solutions require high R&D and production costs, which do not meet the production and market demand of twisted nematic liquid crystal displays (TN-LCD) in the mid- and low-end display field.
[0004] Therefore, it is urgent to find a new solution to improve the electro-optical characteristics of TN-LCD. Summary of the invention
[0005] The purpose of one or more embodiments of this specification is to provide a twisted nematic liquid crystal cell, a display device and a preparation method, so as to 2 O 3 Nanoparticles are doped into liquid crystal to improve the electro-optical properties of TN-LCD.
[0006] To solve the above technical problems, one or more embodiments of this specification are implemented as follows:
[0007] In a first aspect, a twisted nematic liquid crystal box is proposed, comprising: a first substrate, a second substrate disposed opposite to the first substrate, a sealant between the first substrate and the second substrate, and a liquid crystal layer filled between the first substrate and the second substrate and enclosed by the sealant; wherein the nematic liquid crystal in the liquid crystal layer is doped with a specific concentration of composite γ-Fe wrapped by oleic acid 2 O 3 Nanoparticles.
[0008] Optionally, the nematic liquid crystal in the liquid crystal layer is doped with γ-Fe 2 O 3The concentration range of the nanoparticles is: 0.0150wt%-0.1540wt%, 0.2400wt%.
[0009] Optionally, the nematic liquid crystal in the liquid crystal layer is doped with γ-Fe 2 O 3 The optimal concentration of nanoparticles is: 0.0304wt%.
[0010] Optionally, the composite γ-Fe 2 O 3 The diameter of the nanoparticles is 12 nm, wherein the average diameter of the nanoparticle core is 10 nm, and the average thickness of the encapsulated oleic acid is 2 nm.
[0011] In a second aspect, a twisted nematic liquid crystal display device is provided, comprising the twisted nematic liquid crystal cell.
[0012] In a third aspect, a method for manufacturing the twisted nematic liquid crystal cell is proposed, comprising:
[0013] γ-Fe coated with oleic acid 2 O 3 Nanoparticles were prepared by ultrasonic treatment at room temperature for 30 minutes. The diameter of the composite nanoparticles was 12 nm, wherein the average diameter of the nanoparticle core was 10 nm and the average thickness of the oleic acid was 2 nm.
[0014] Preparation of oleic acid-coated n-hexyl magnetic liquid doping solution: a small amount of composite γ-Fe 2 O 3 The nanoparticles were mixed into volatile n-hexane, sonicated for 40 minutes, and the mixture was centrifuged at 5000 rpm for 30 minutes to obtain a stable n-hexane magnetic liquid.
[0015] Preparation of composite γ-Fe 2 O 3 Mixture of nanoparticles and liquid crystal materials: Take equal volumes of n-hexane and pre-doped liquid crystal and mix them evenly. Then, add a small amount of prepared n-hexane-based magnetic liquid. Heat the mixture to about 10°C above the clearing point temperature of the pre-doped negative liquid crystal. Use an oscillating shaker to treat the mixture until all the n-hexane evaporates. Then, a composite γ-Fe doped with oleic acid at a concentration of 0.0304 wt% is obtained. 2 O 3 A liquid crystal mixture;
[0016] The obtained composite γ-Fe 2 O 3 The nanoparticle liquid crystal mixture is poured into a 4-μm-thick twisted nematic phase liquid crystal box, and a frame sealing adhesive is coated, and the twisted nematic phase liquid crystal box is obtained after ultraviolet light curing.
[0017] It can be seen from the technical solutions provided by one or more embodiments of the present specification that the twisted nematic liquid crystal box in the solution includes: a first substrate, a second substrate arranged opposite to the first substrate, a sealant located between the first substrate and the second substrate, and a liquid crystal layer filled in the area between the first substrate and the second substrate and enclosed by the sealant; wherein the nematic liquid crystal in the liquid crystal layer is doped with a specific concentration of composite γ-Fe wrapped by oleic acid 2 O 3 Nanoparticles. 2 O 3 Nanoparticles are doped into liquid crystal to improve the electro-optical properties of TN-LCD, especially when the doping concentration is 0.0304wt%, the transmittance of the nematic liquid crystal cell is high. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more clearly illustrate one or more embodiments of this specification or the technical solutions in the prior art, the drawings required for use in the description of one or more embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in this specification. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0019] Figure 1 It is a simple structural schematic diagram of a twisted nematic liquid crystal box provided in an embodiment of this specification.
[0020] Figure 2 The examples of this specification provide different concentrations of γ-Fe doped 2 O 3 Schematic diagram of the electro-optical curve of the nanoparticle liquid crystal cell at room temperature.
[0021] Figure 3 This is a schematic diagram of the steps of a method for manufacturing the above-mentioned twisted nematic liquid crystal box provided in an embodiment of the present specification.
[0022] Figure 4 The embodiments of this specification also provide a schematic diagram of an optical path for measuring the electro-optical properties of liquid crystal materials. DETAILED DESCRIPTION
[0023] In order to enable those skilled in the art to better understand the technical solutions in this specification, the technical solutions in one or more embodiments of this specification will be clearly and completely described below in conjunction with the drawings in one or more embodiments of this specification. Obviously, the one or more embodiments described are only part of the embodiments of this specification, not all of the embodiments. Based on one or more embodiments in this specification, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of this document.
[0024] The following is an explanation of the terms involved in the embodiments of this specification.
[0025] TN-LCD: The rubbing directions of the upper and lower substrate alignment layers are perpendicular to each other. When no voltage is applied, the liquid crystal molecules are arranged in a 90° twist from the lower substrate to the upper substrate and have optical rotation properties to light.
[0026] Electro-optical characteristics: The characteristics of TN-LCD that change its optical transmittance when a certain voltage is applied. Under the action of an external electric field, the orientation of the liquid crystal changes, and the optical delay also changes, resulting in changes in the intensity of light passing through the liquid crystal layer. The threshold voltage, saturation voltage and steepness of the display can be obtained through the electro-optical characteristic curve.
[0027] Threshold voltage: The voltage value corresponding to when the transmittance of TN-LCD reaches 10% (normally black mode) or 90% (normally white mode).
[0028] Saturation voltage: The voltage value corresponding to when the transmittance of TN-LCD reaches 90% (normally black mode) or 10% (normally white mode).
[0029] Steepness: The ratio of saturation voltage to threshold voltage.
[0030] When conceiving this solution, the cost and difficulty of improving the electro-optical characteristics of the liquid crystal box mentioned in the background technology were taken into consideration. Therefore, this application improves the characteristics of liquid crystal materials by means of doping to improve the electro-optical characteristics of TN-LCD.
[0031] Embodiment 1
[0032] Reference Figure 1 FIG. 1 is a schematic diagram of a simple structure of a twisted nematic liquid crystal cell provided in an embodiment of the present specification. The liquid crystal cell may include the following structural components:
[0033] A first substrate 102, a second substrate 104 disposed opposite to the first substrate 102, a sealant 106 located between the first substrate 102 and the second substrate 104, and a liquid crystal layer 108 filled in the area between the first substrate 102 and the second substrate 104 and enclosed by the sealant 106; wherein the nematic liquid crystal in the liquid crystal layer 108 is doped with a specific concentration of composite γ-Fe wrapped by oleic acid 2 O 3 Nanoparticle 110.
[0034] Reference Figure 1 The small black dots indicate the composite γ-Fe doped in the liquid crystal. 2 O 3 Nanoparticles. After multiple experiments in this scheme, it was confirmed that the ferromagnetic γ-Fe doped in liquid crystal 2 O 3 Nanoparticles, under the external field, produce a magnetization effect, adsorb and disperse impurity ions in the liquid crystal system, and can improve the magnetic order of the entire liquid crystal system, thereby improving the dynamic response problems such as image retention and motion tailing of nematic liquid crystal displays. In this way, the transmittance of the doped liquid crystal material has been greatly improved, but the other physical parameters are similar to those of the pure liquid crystal material, indicating that doping with a small amount of nanoparticles will not greatly change the physical properties of the liquid crystal material, but will also help to improve the performance of the liquid crystal material. Therefore, by doping a specific concentration of γ-Fe in the liquid crystal of the liquid crystal box, 2 O 3 Nanoparticles can improve and enhance the electro-optical properties of liquid crystal cells.
[0035] Furthermore, in a specific implementation, the nematic liquid crystal in the liquid crystal layer is doped with γ-Fe 2 O 3 The concentration range of the nanoparticles is: 0.0150wt%-0.1540wt%, 0.2400wt%.
[0036] Furthermore, the nematic liquid crystal in the liquid crystal layer is doped with γ-Fe 2 O 3 The optimal concentration of nanoparticles is: 0.0304wt%.
[0037] Reference Figure 2 As shown, different concentrations of γ-Fe 2 O 3 The electro-optical curve of the nanoparticle liquid crystal cell at room temperature, where the horizontal axis is the applied voltage and the vertical axis is the absolute transmission intensity. Figure 2It can be seen that the electro-optical curves of the liquid crystal cells with doping concentrations ranging from 0.0150wt% to 0.1540wt% and 0.2400wt% are better, and a higher transmittance can be guaranteed when the threshold voltage is not high. In particular, when the doping concentration is 0.0304wt%, the transmittance of the liquid crystal cell is the best, reaching a transmittance of about 43%. It can be seen that the electro-optical characteristics of the nematic liquid crystal cell are well improved and enhanced.
[0038] Optionally, the composite γ-Fe 2 O 3 The diameter of the nanoparticles is 12nm, of which the average diameter of the nanoparticle core is 10nm and the average thickness of the oleic acid is 2nm. Under the size of the nanoparticles, uniform doping can be well achieved, further ensuring a large transmittance.
[0039] At the same time, the present specification also provides a twisted nematic liquid crystal display device, including the above Figure 1 The twisted nematic liquid crystal cell shown in FIG. In addition, other existing components may also be included, such as a backlight source, a driving backplane, and the like.
[0040] Reference Figure 3 As shown, the embodiments of this specification also provide a method for manufacturing the above-mentioned twisted nematic liquid crystal box, which method may include at least the following main steps. Other steps may not appear in the embodiments of this specification, but it does not mean that these steps do not exist.
[0041] Step 302: Coating γ-Fe with oleic acid 2 O 3 Nanoparticles were prepared and ultrasonically treated at room temperature for 30 minutes. The diameter of the nanoparticles after composite was 12 nm, wherein the average diameter of the nanoparticle core was 10 nm, and the average thickness of the encapsulated oleic acid was 2 nm.
[0042] Among them, in the examples of this specification, the metal oxide γ-Fe 2 O 3 Nanoparticles can be synthesized by chemical coprecipitation of FeOOH and Mg(OH) 2 The resulting hydroxide precursor is then treated with FeCl 2 Solution treatment, final Mg(OH) 2 Compound dissolution, FeOOH dehydration and conversion to γ-Fe 2 O 3 Nanoparticles.
[0043] Preparation of γ-Fe 2 O 3When the nanoparticles are doped with nematic liquid crystal materials, in order to obtain a stable and uniform liquid crystal mixed system, the nanoparticles are firstly coated with oleic acid and ultrasonically treated at room temperature for 30 minutes. 2 O 3 / oleic acid) has a diameter of 12nm, of which the average diameter of the nanoparticle core is 10nm, and the average thickness of the encapsulated oleic acid is 2nm.
[0044] Step 304: Prepare oleic acid-coated n-hexyl magnetic liquid doping solution: Add a small amount of composite γ-Fe 2 O 3 The nanoparticles were mixed into volatile n-hexane, sonicated for 40 minutes, and the mixture was centrifuged at 5000 rpm for 30 minutes to obtain a stable n-hexane magnetic liquid.
[0045] Step 306: Preparation of composite γ-Fe 2 O 3 Mixture of nanoparticles and liquid crystal materials: Take equal volumes of n-hexane and pre-doped liquid crystal and mix them evenly. Then, add a small amount of prepared n-hexane-based magnetic liquid. Heat the mixture to about 10°C above the clearing point temperature of the pre-doped negative liquid crystal. Use an oscillating shaker to treat the mixture until all the n-hexane evaporates. Then, a composite γ-Fe doped with oleic acid at a concentration of 0.0304 wt% is obtained. 2 O 3 A liquid crystal mixture;
[0046] The mixed liquid is uniform and has no precipitation, indicating that the nanoparticles can be well dispersed in the liquid crystal system.
[0047] Step 308: The obtained composite γ-Fe 2 O 3 The nanoparticle liquid crystal mixture is poured into a 4-μm-thick twisted nematic phase liquid crystal box, and a frame sealing adhesive is coated, and the twisted nematic phase liquid crystal box is obtained after ultraviolet light curing.
[0048] Will γ-Fe 2 O 3 The nanoparticle-doped nematic liquid crystal is poured into a 4-μm-thick twisted nematic liquid crystal box (TN box), coated with sealing glue, and cured under ultraviolet light.
[0049] Further, you can press Figure 4 The optical path shown in the figure uses an optical power meter to measure the electro-optical properties of liquid crystal materials with different doping concentrations. The results are as follows Figure 2 As shown in the figure, γ-Fe 2 O 3The addition of nanoparticles has an impact on the performance of liquid crystal materials. When the concentration is appropriate (experiments show that the concentration is close to 0.0304wt%), the electro-optical properties of the material are significantly improved. 2 O 3 The transmission intensity of liquid crystal materials can be increased by about 12μw compared to pure liquid crystal.
[0050] Through the technical solution of this manual, composite γ-Fe 2 O 3 The nanoparticles were doped with nematic liquid crystals (e.g. E7) and poured into a twisted nematic liquid crystal cell for a series of electro-optical property measurements. 2 O 3 Nanoparticles can effectively improve the electro-optical properties of twisted nematic liquid crystals. Especially doped composite γ-Fe 2 O 3 The electro-optical properties are optimal when the concentration of nanoparticles is 0.0304wt%.
[0051] The above is a description of a specific embodiment of the specification. Other embodiments are within the scope of the appended claims. In some cases, the actions or steps recorded in the claims can be performed in an order different from that in the embodiments and still achieve the desired results. In addition, the processes depicted in the drawings do not necessarily require the specific order or continuous order shown to achieve the desired results. In some embodiments, multitasking and parallel processing are also possible or may be advantageous.
Claims
1. A twisted nematic liquid crystal cell, characterized in that: include: A first substrate, a second substrate arranged opposite to the first substrate, a sealing glue located between the first substrate and the second substrate, and a liquid crystal layer filling the area between the first substrate and the second substrate and enclosed by the sealing glue; wherein the nematic liquid crystal in the liquid crystal layer is doped with composite γ-Fe2O3 nanoparticles wrapped by oleic acid at a concentration of 0.0304wt%, and the composite γ-Fe2O3 nanoparticles produce a magnetization effect under the action of an external field to adsorb impurity ions in the nematic liquid crystal, which can improve the magnetic order of the entire liquid crystal system and improve the transmission intensity of the liquid crystal layer.
2. The twisted nematic liquid crystal cell according to claim 1, characterized in that: The diameter of the composite γ-Fe2O3 nanoparticles is 12 nm, wherein the average diameter of the nanoparticle magnetic core is 10 nm, and the average thickness of the encapsulated oleic acid is 2 nm.
3. A twisted nematic liquid crystal display device, characterized in that: It comprises the twisted nematic liquid crystal cell as claimed in claim 1 or 2.
4. A method for manufacturing the twisted nematic liquid crystal cell according to claim 1 or 2, characterized in that: include: γ-Fe2O3 nanoparticles were coated with oleic acid and ultrasonically treated at room temperature for 30 minutes. The diameter of the composite nanoparticles was 12nm, of which the average diameter of the nanoparticle core was 10nm and the average thickness of the coated oleic acid was 2nm. Preparation of oleic acid-coated n-hexyl magnetic liquid doping solution: a small amount of composite γ-Fe2O3 nanoparticles was mixed into volatile n-hexane, ultrasonicated for 40 minutes, and the mixture was centrifuged at 5000 rpm for 30 minutes to obtain a stable n-hexyl magnetic liquid; Prepare a mixed solution of composite γ-Fe2O3 nanoparticles and liquid crystal materials: take equal volumes of n-hexane and pre-doped liquid crystal and mix them, perform ultrasonic treatment to make the two liquids mix evenly, then mix a small amount of prepared n-hexane-based magnetic liquid, heat the temperature to about 10°C above the clearing point temperature of the pre-doped positive liquid crystal, use an oscillating shaker to treat, wait for all the n-hexane to volatilize, and obtain a liquid crystal mixture doped with 0.0304wt% of oleic acid-wrapped composite γ-Fe2O3; The obtained liquid crystal mixture doped with composite γ-Fe2O3 nanoparticles is poured into a 4μm thick twisted nematic phase liquid crystal box, and a frame sealing glue is coated. After ultraviolet light curing, a twisted nematic phase liquid crystal box is obtained. The composite γ-Fe2O3 nanoparticles produce a magnetization effect under the action of an external field to adsorb impurity ions in the nematic phase liquid crystal, which can improve the magnetic order of the entire liquid crystal system and improve the transmission intensity of the twisted nematic phase liquid crystal box.
Citation Information
Patent Citations
Liquid crystal display panel and manufacturing method thereof and liquid crystal display device
CN103091891A
Method for preparing diluted magnetic polymer dispersed liquid crystal through photo-initiated free radical tandem reaction and product thereof
CN114149550A